Potentiality or Capacity? Agamben’s Missing Subjects - Power, Nina (Filozofski vestnik, 2016)
Agamben’s paradoxical treatments of potentiality seem to leave little room for any robust theory of the subject, political or otherwise. His Aristotelian conception of potentiality entails, in the highest instance, “that potentiality constitutively is the potentiality not to (do or be),” which suggests that even if potential is realized, it is realized only by its lack of activity. Agamben’s Aristotelianism is a thread that runs throughout his work, and by looking back to The Man Without Content, particularly his discussion of Marx, it is clear that the framework of potentiality means that it is impossible for him to see in Marx anything other than an odd combination of a “metaphysics of will”, and man simply as a kind of natural, living being. This in turn shapes his later discussion in Homo Sacer of the entry of zoe into the polis, which founds Agamben’s entire claim vis-a-vis bare life. His wager, namely that the question “’In what way does the living being have language?” corresponds exactly to the question “In what way does bare life dwell in the polis?’”, equates the living being with its political, linguistic, and natural potentialities so completely that there seems to be no room for any kind of historically anomalous or collectively unprecedented subject, one that would break with history or disrupt everyday order. Agamben’s work could easily be criticized from the standpoint of a Marxism that would stress the constructed nature of human potential and the necessity to think through forms of organization from within shifts in the nature of work. However, in order to stay closer to Agamben’s Aristotelianism, it is far more productive to compare him to a thinker for whom questions of linguistic capacity and politics are also central, and also stem from a certain complex relation to naturalism, namely Paolo Virno. This paper will thus, via a careful reading of Agamben’s Aristotelian conception of praxis and potentiality alongside Virno’s work on the relation between language and labour, demonstrate the constitutive reasons why Agamben cannot consider any kind of substantial notion of the subject, and why Virno’s more nuanced conception of capacity, which draws upon both rationalist and naturalist theories of the subject might constitute a more relevant alternative.